Health Literacy and Acceptance of COVID-19 Preventive Measures and Vaccination in the European Union: A Scoping Review - Evridiki Vasileia; George Koulierakis; Theodoros Fouskas; Angeliki Liarigkovinou (Health Literacy Research and Practice)
Background Health literacy is becoming increasingly important in the field of public health as it contributes to individuals' social empowerment. During the coronavirus disease 2019 (COVID-19) pandemic, preventive measures (mask usage, physical distancing, hand washing) and vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) shaped the degree of infection of the population, and their acceptance was associated with a multitude of factors, health literacy included. The aim of this scoping review is to explore the impact of all health literacy dimensions (namely, understanding, access, evaluation and application of health information) on accepting preventive measures and vaccination against SARS-CoV-2 among adult European citizens. Methods A literature search on three different databases was conducted from July 2022 to December 2022. Key Results A total of 154 articles were initially identified, which were rigorously assessed by two reviewers. Ten studies that met the inclusion criteria were analyzed. The results showed that health literacy played an important role in accepting preventive measures and vaccination as well as in rating health information related to the coronavirus. Discussion Health literacy is a positive predictor of coronavirus prophylaxis and could be incorporated into public health policies to appropriately control future health crises. [HLRP: Health Literacy Research and Practice. 2025;9(1):e46–e55.]